Application of Internet of Things (IoT) Data Logger: A Comparison of Different Techniques for Assessing Ambient Air Pollution Levels - Kar Kar, Chong; Rosli, Mohd Arif; Sadun, Amirul Syafiq; Sabarudin, Nur Azizah (Progress in Engineering Application and Technology, 2022)
Air pollution has an impact on the daily lives of humans and the standard of living. It presents a danger to the environment and quality of life. There is an essential need to monitor air quality because of growing industrial activity in recent years. This study is to implement an IoT-based data logger (IoTDL) for the E-sampler dual ambient monitor that collects raw data from Air Pollution Index (API) data measurement device. The MA-01 IoT Magic Kit-ESP8266 was developed to build the air pollution monitoring system. Its major purpose is to access the internet through the Blynk application which is one of the IoT mobile applications that enables a wireless connection between the equipment and the Blynk application. The air pollution monitoring system was created to monitor and evaluate air quality. This study is also looking to verify the reliability of the IoTDL method in the real-time mobile application for the particulate concentration of particulate matter smaller than 2.5 µm (PM2.5), sample air flow rate, ambient temperature, ambient barometric pressure, external ambient relative humidity, internal filter sample relative humidity, wind speed, and wind direction in comparison on the conventional framework for the E-sampler. The comparison is made between the IoTDL method and the conventional framework for the E-sampler. Both techniques have been discussed in detail in this study. In summary, the results illustrate that the techniques correspond well.